Hukum Kepemimpinan Wanita dalam Al-Qur’an: : Analisis Kata Qawwām terhadap Kriteria Kepemimpinan - Al Faruq, Abdul Qudus; Sumarkan; Nafi Mubarok (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2023)
A textualist interpretation of Surah An-Nisa verse 34, particularly regarding the term Qawwām has often fueled issues of discrimination against women. This verse is frequently cited as a basis for restricting women's roles across various spheres, from social involvement to administrative duties. This study employs a qualitative, library-based approach, incorporating thematic analysis, linguistic studies, and historical context related to sabab nuzul and sabab wurud. Findings indicate that Islam does not explicitly prohibit women from leadership roles in governance, social settings, economics, or religious spheres, as long as specific conditions in line with Islamic Criteria are met. By exploring narratives such as Maryam’s service in Baitul Maqdis and Queen Bilqis's leadership in the Qur’an, it is evident that women’s leadership can succeed when rooted in integrity. Such roles are often contextually motivated by necessity and circumstance. A woman in leadership, however, is expected to uphold respect within her household, demonstrating balance and commitment to her familial responsibilities.